Analisis Yuridis Ketentuan Pembuatan Surat Wasiat Berkaitan dengan Pembagian Warisan Apabila Tidak ada Keluarga Sedarah Pada Garis Lurus Ke atas dan Ke Bawah Sesuai dengan Ketentuan KUH Perdata dan KHI - Jihan Wijayanti, Nur`aini; Rifana, Ruri (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
There are many Indonesian people who do not understand the provisions regarding the making of a will, especially regarding a will made by a testator who does not have a blood relative, either in a straight line upwards or downwards. This study was conducted to determine the provisions for making a will according to the Civil Code, KHI, and the provisions for making a will if there is no blood relative. The research method used is normative juridical by reviewing secondary data in the form of laws and regulations, books and journals. The results of the analysis based on the Civil Code and KHI, a will must meet several requirements, namely being sane, adult, the property that is bequeathed belongs to the testator, avoiding several prohibitions, and must meet the provisions of Legitimae Portie. Based on the Civil Code, the making of a will by a testator who does not have heirs in the blood relative in a straight line upwards and downwards is permitted, but it should still be discussed with other heirs. Meanwhile, based on KHI, it is permitted if there is approval from the heirs.